Fungsi Sosial-Ekonomi Pasar Tradisional (Studi Tentang Pasar Karah Kec. Jambangan, Kota Surabaya) - Triana Rosalina Noor (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang Indonesia, 2017)
This study examines about traditional markets function in social and economic community around. The object is Karah Traditional Market, Kec. Jambangan, Surabaya. This study uses qualitative descriptive method involving as many as 30 respondents, which are 15 buyers and 15 sellers conduct transactions in the Karah Traditional Market and used incidental sampling. The results of this study indicate that the social function of traditional markets Karah for communities that exist around the market first is a function of social relations, the market used as a strengthening of social relationships between sellers and buyers. Other activities are also the traders and buyers often discuss the latest news that busy discussed in public. The second social function is a function of socialization / exchange information which market participants interact with each other and make the process of delivering information and learning. As for economy functions, the first is to people who are buying and selling function which becomes meeting community needs. The second function is to bring jobs for the people around, because it absorbs jobs for the surrounding communities. The third function is the function adds to the welfare of society, the intention is Karah Market provides an additional income for the economic welfare of the community.